Socialization on the Importance of Saving for the Young Generation to Students at Baiturrahman Elementary School Tasikmalaya City - Grida Saktian Laksito (Research Collaboration Community (RCC), 2021)
The socialization of the love of saving is a form of community service, with the aim of helping elementary school students to increase their understanding of the importance of saving from an early age to SD Baiturrahman Tasikmalaya City. Saving in various perspectives is highly recommended because the habit of living extravagantly will only leave difficulties in the future, in accordance with the motto of saving money on a rich base. This method of community service activity begins with the preparation stage and field survey. This survey stage begins with direct discussions with the Principal of SD Baiturrahman Tasikmalaya City to identify student behavior in managing finances given by their parents as provisions at school, after knowing the behavior of students in managing their finances, the next activity will be carried out face to face using the method of delivering socialization materials with counseling techniques, questions and answers, quizzes, creations to make piggy banks, as well as by adding games. The results of this study are to provide knowledge of participants who are SD Baiturrahman Tasikmalaya City, where previously they were less enthusiastic in saving and getting used to living extravagantly. After participating in the socialization activity for liking to save, students are able to distinguish between necessities and wants, learn how to treat the two items and can apply saving behavior from an early age.